Evaluating testcross performance and genetic divergence of lines derived from reciprocal tropical maize composites - Menkir, A.; Kling, J.G.; Anjorin, B.; Ladejobi, F.; Gedil, Melaku A (2015)
The development of hybrids with enhanced expression of heterosis depends on the genetic background of the source population and the effectiveness of a breeding scheme used to identify and use divergent inbred lines with good combining ability. The present study was conducted to examine the potential of improved tropical reciprocal composites as sources of inbred lines for developing productive hybrids. Thirty-six S4 lines derived from the third RRS cycle of each composite were crossed in pairs to form 36 testcrosses, which were evaluated along with commonly grown commercial hybrids in Nigeria across nine test environments. Results showed consistent ranking of testcrosses for grain yield and other traits across the diverse test environments. The best 22 testcrosses produced 21% to 51% more grain yields than the highest yielding commercial hybrid. Several testcrosses combined high grain yields with other desirable agronomic traits. The SSR and SNP markers used in the present study detected a broad range of genetic diversity among the 72 S4 lines, which was structured along the two composites. The two markers portrayed similar trends in determining genetic distance estimates and detecting composite-specific alleles in the S4 lines. These results highlight the potential of improved reciprocal composites as sources of new and divergent parents for developing productive hybrids and as sources of novel alleles for broadening and diversifying the genetic base of adapted germplasm to sustain genetic gain in productivity of hybrids in WCA.